Design of Wideband Backed Cavity Volumetric Dumbbell-Shaped Slot Antenna Using SIW Technology - Subrahmanyam K,; Bhanu Sri Mounika K,; Keerthana M,; Rama Rao G,; Prathusha A,; Ramprasad Ravula, (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The growing demand for high-performance wireless communication has necessitated advanced antenna designs with improved bandwidth and efficiency. This study presents a novel dumbbell-shaped slot antenna based on Substrate Integrated Waveguide (SIW) technology. The antenna is engineered to provide extended bandwidth and enhanced radiation characteristics, optimized using ANSYS HFSS simulation software. The results indicate a wideband operation spanning 14.95 GHz to 16.50 GHz, achieving a 1.55 GHz bandwidth and a maximum gain of 5.4 dB at 16.50 GHz. These characteristics make the design a strong candidate for next-generation wireless communication applications.
Keywords: Dumbbell slot antenna; RF design; SIW; HFSS; Wideband performance